THE IMPORTANCE OF CHARACTER BUILDING IN THE TERM OF EDUCATION TOWARDS THE NATIONS’ IMPROVEMENT - Normawati, Normawati; Hasriana, Hasriana (IQRA JURNAL ILMU KEPENDIDIKAN & KEISLAMAN, 2018)
The objectives of this article are to present description of the meaning of character and character building, the importance of character building in the term of education and also the role of character building towards the nations' improvement. The writer found that character is the actual state of an individual, which distinguishes himself from other individuals. Meanwhile, character building is a system that instills the values of character to an individual, includes: science, awareness, willingness and action to be able to carry out those values both to God the Almighty, himself, others, his environment and also to the nation and country. Character building is an education that is implemented anyone personality to be a good person. Furthermore, by applying learning centered at the learners, it will produce an excellent learner not only for their cognitive but also for their character. Then, they will be able to face the problems and challenges in their life.In addition,to strengthen the moral character of the nation, character education from an early age is needed. Of course, starting from the moral education in the family, school and neighborhood. The writer suggest that the government should prepare some policies that are directly related to education such as preparing a better education curriculumin order the old generation can have an excellent character. And also to the formal education institutions (schools)as the right facilitation for developing generation characters, should be able to prepare certain approach including curriculum development and effective innovation as teaching-learning method.